Design of PIFA Antenna Using Systematic Tuning for Long Range Communication - Sabila, Liya Yusrina; Prakoso, Teguh; Riyadi, Munawar Agus (Universitas Ahmad Dahlan, 2023)
Communication with a wireless system is one of the mainstays of communication so that communication integration is achieved. In this application, of course, an antenna is needed to send information waves to the receiver. It is also hoped that the antenna can be integrated with other components into an integrated system. There are several challenges that need to be answered to make this happen. Namely, the size of the antenna is small and the shape of the antenna can adjust to the shape of the object being integrated, for example a circle or cylinder shape. The antenna chosen to realize this challenge is the Planar Inverted F Antenna (PIFA). PIFA antennas are widely used in communication devices because their shape and size can be adjusted to the dimensions of the device. The technique used to create curved shapes is a conformal technique. To streamline the antenna design steps, the system tuning method is applied when simulating the design. The results achieved use a system tuning method which can reduce the experimental steps to just 6 experimental steps. The antenna designed works in the frequency range 916.9 – 933 MHz, the resonant frequency of 925.6 MHz with S11 is -12.5 dB, bandwidth 16.1 MHz, and the radiation pattern is omnidirectional.